Heart failure, ventricular dysfunction and risk factor prevalence in Australian Aboriginal peoples: the Heart of the Heart Study. Issue 21 (11th August 2012) - McGrady, Michele; Krum, Henry; Carrington, Melinda J; Stewart, Simon; Zeitz, Christopher; Lee, Geraldine A; Marwick, Thomas H; Haluska, Brian A; Brown, Alex
Abstract : Background: Limited strategies have been developed to evaluate and address the alarming discrepancy in early mortality between Indigenous and non-Indigenous populations. Objective: To assess heart failure (HF), HF risk factors and document cardiac characteristics in an Australian Aboriginal population. Design, setting, participants: Adults were enrolled across six Aboriginal communities in Central Australia. They undertook comprehensive cardiovascular assessments, including echocardiography, to determine HF status, asymptomatic ventricular dysfunction and underlying risk factor profile. Results: Of 436 participants (mean age 44±14 years; 64% women) enrolled, 5.3% (95% CI 3.2% to 7.5%) were diagnosed with HF, only 35% of whom had a pre-existing HF diagnosis. Asymptomatic left ventricular dysfunction (ALVD) was seen in 13% (95% CI 9.4% to 15.7%) of the population. Estimates of HF risk factor prevalence were as follows: body mass index (BMI) ≥30 kg/m 2 42%, hypertension 41%, diabetes mellitus 40%, coronary artery disease (CAD) 7% and history of acute rheumatic fever or rheumatic heart disease 7%. In logistic regression analysis (after adjustment for age and gender), HF was associated with CAD (OR=9.6, p<0.001), diabetes (OR=5.4, p=0.002), hypertension (OR=4.8, p=0.006), BMI ≥30 kg/m 2 (OR=2.9, p=0.02), acute rheumatic fever or rheumatic heart disease (OR=5.6, p=0.001) and B-type natriuretic peptide (OR=1.02, p<0.001). Conclusion: The burden of HF, ALVD and risk factors in this population was extremely high. This study highlights potentially modifiable targets on which to focus resources and screening strategies to prevent HF in this high-risk Indigenous population.